Analisis Variasi Temperatur Aktivasi dengan Agen Potassium Silicate (K2SiO3) terhadap Sifat Listrik Arang Aktif Tandan Aren (Arenga pinnata Merr.) - Wahyuni, Kiki; Anas, Muhammad; M, Hunaidah (Jurusan Pendidikan Fisika, 2020)
This research aims to determine the effect of variations of temperature activation with the Potassium Silicate (K2SiO3) agent on the electrical conductivity and capasitance of activated carbon from the sugar palm bunches (Arenga Pinnata Merr.). Activated carbon from bunches of sugar palm acquired in four steps: 1) preparation; 2) carbonization using the pyrolysis reactor with temperature of 300oC-400oC for 8 hours; 3) chemical activation using of potassium silicate (K2SiO3) activator in weight ratio of 2: 1 for 12 hours; and 4) physical activation using the electric furnace for 30 minutes with temperature variation of 600oC, 650oC, 700oC, 750oC and 800oC. Electrical conductivity was determined and analyzed by the I-V method, the capasitance was determined by using a RC circuit (Resistor Capasitor). The highest electrical conductivity and capasitance were at the temperature of 800oC that equal to 1.75 x 10-1 Î©-1m-1 and 102.07 nF respectively.